Barium sulfate/regenerated cellulose composite fiber with X-ray radiation resistance. (November 2015) - Qu, Lijun; Tian, Mingwei; Zhang, Xiansheng; Guo, Xiaoqing; Zhu, Shifeng; Han, Guangting; Li, Changlei
In this article, submicron barium sulfate particles, as the radiation-resistant component, were incorporated into regenerated cellulose spinning solution. Then a series of X-ray radiation-resistant fibers were fabricated via a primarily industrialized wet-spinning trail, and the resultant fibers were knitted into fabrics by knitting loom. The morphology and structure of the fibers were studied with the aid of scanning electron micrography, Fourier-transform infrared spectroscopy, and X-ray diffraction. The composite fibers exhibited reasonably good properties, which met the criteria of mechanical requirements of commercial textiles—dry breaking strength and elongation (>1.5 cN/dtex and 26%) and wet breaking strength and elongation (>1.4 cN/dtex and 22%) and permanent laundry-resistant abilities even after being washed 20 times. An effective and feasible X-ray radiation-resistant method, the medical digital X-ray photography system, was proposed to evaluate the radiation resistance of the composite fiber and its fabric. The X-ray attenuation ratio of the sample tended to increase with increasing barium sulfate content and finally reached a dose of a 0.1 mmPb lead equivalent. Therefore, these fibers and fabrics can be utilized as the base materials for X-ray radiation-resistant lightweight apparel and detective surgical yarn.